COVID/HIV Co-Infection: A Syndemic Perspective on What to Ask and How to Answer - Hailay Abrha Gesesew; Hailay Abrha Gesesew; Lillian Mwanri; Jacqueline H. Stephens; Kifle Woldemichael; Paul Ward (Frontiers Media S.A., 2021)
The present commentary explored the intersecting nature of the COVID-19 and HIV pandemics to identify a shared research agenda using a syndemic approach. The research agenda posits the following questions. Questions around HIV infection, transmission, and diagnosis include: (i) molecular, genetic, clinical, and environmental assessments of COVID-19 in people living with HIV, (ii) alternative options for facility-based HIV testing services such as self- and home-based HIV testing, and (iii) COVID-19 related sexual violence and mental health on HIV transmission and early diagnosis. These and related questions could be assessed using Biopsychosocial and socio-ecological models. Questions around HIV treatment include: (i) the effect of COVID-19 on HIV treatment services, (ii) alternative options for facility-based treatment provision such as community-based antiretroviral therapy groups, and (iii) equitable distribution of treatment and vaccines for COVID-19, if successful. Bickman's logic model and the social determinants of health framework could guide these issues. The impact of stigma, the role of leveraging lessons on sustained intra-behavioral change, the role of medical mistrust and conspiracy beliefs, and the role of digital health on integrated management of HIV care and spectrum of care of COVID-19 need assessment using several frameworks including Goffman's stigma framework, Luhmann's Trust theory, and Gidden's theory of structuration. In conclusion, the potential research agenda of this commentary encompasses a variety of research fields and disciplinary areas-clinicians, laboratory scientists, public health practitioners, health economists, and psychologists-, and suggests several theoretical frameworks to guide examination of complex issues comprehensively.